Impact of congenital heart disease on outcomes among pediatric patients hospitalized for influenza infection - Laxmi V. Ghimire; Fu-Sheng Chou; Anita J. Moon-Grady (BMC, 2020)
Abstract Background Young children and those with chronic medical conditions are at risk for complications of influenza including cardiopulmonary compromise. Here we aim to examine risks of mortality, clinical complications in children with congenital heart disease (CHD) hospitalized for influenza. Methods We analyzed data from in-hospital pediatric patients from 2003, 2006, 2009, 2012 and 2016 using the nationally representative Kids Inpatient Database (KID). We included children 1 year and older and used weighted data to compare the incidence of in-hospital mortality and rates of complications such as respiratory failure, acute kidney injury, need for mechanical ventilation, arrhythmias and myocarditis. Results Data from the KID estimated 125,470 children who were admitted with a diagnosis of influenza infection. Out of those, 2174(1.73%) patients had discharge diagnosis of CHD. Children with CHD who required hospitalization for influenza had higher in-hospital mortality (2.0% vs 0.5%), with an adjusted OR (aOR) of 2.8 (95% CI: 1.7-4.5). Additionally, acute respiratory failure and acute kidney failure were more likely among patients with CHD, with aOR of 1.8 (95% CI: 1.5-2.2) and aOR of 2.2 (95% CI: 1.5-3.1), respectively. Similarly, the rate of mechanical ventilatory support was higher in patients with CHD compared to those without, 14.1% vs 5.6%, aOR of 1.9 (95% CI: 1.6-2.3). Median length of hospital stay in children with CHD was longer than those without CHD [4 (IQR: 2-8) days vs. 2 (IQR: 2-4) days]. Outcomes were similar between those with severe vs non-severe CHD. Conclusions Children with CHD who require hospital admission for influenza are at significantly increased risk for in-hospital mortality, morbidities, emphasizing the need to reinforce preventative measures (e.g. vaccination, personal hygiene) in this particularly vulnerable population.